Pengaruh Tingkat Pendidikan, Pertumbuhan Ekonomi, dan Jumlah Penduduk terhadap Tingkat Kemiskinan di Kabupaten Hulu Sungai Tengah - Muhammad Alfian Noor; Siti Mutmainah Zulfaridatulyaqin (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Poverty is a major problem in the economy. Therefore it needs to be studied tofind solutions to reduce poverty in an area. This study aims to determine the effect ofeducation level, economic growth, and whether the population has a significant effecton poverty levels in the Hulu Sungai Tengah Regency.This research was carried out in Hulu Sungai Tengah Regency using multiplelinear regression with secondary data obtained from BPS South Kalimantan and BPSin Hulu Sungai Tengah Regency using time series data from 2001 to 2017. The datawas analyzed using Eviews by looking at the magnitude of the coefficient ofdetermination test (R2test), simultaneous test (F test), and partial test (T-test). Adjusted R 2, which shows the effect of independent variables on the dependentvariable, has a strong effect of 79,42%. THE probability F count of 0,000025 issmaller than 0,05, which means the estimated regression model is worth using forresearch. The results obtained from research conducted using the T-test showed thatthe level of education and the number of inhabitants had a significant effect, buteconomic growth had no significant effect on poverty levels in the Hulu SungaiTengah Regency.